Peer Group Education Meningkatkan Pengetahuan Dan Perilaku Sadari Remaja Putri SMAKN ST. Thomas Morus Ende - Khrispina Owa; Maria Salestina Sekunda; Irwan Budiana (Akademi Kebidanan Aifa Husada Madura, 2020)
Breast cancer is a type of malignant neoplasm that attacks breast tissue by mutating from previously normal cells that have anti-social properties against normal cells of the body (Depkes, 2007). Breast cancer as one of the second highest causes of death in women in Indonesia. Doing breast self-examination (SaDaRi) is considered to be very effective in detecting early breast cancer events. The problem that is happening right now is that the public's knowledge about SaDaRi is still lacking. a peer education is one of the activities of youth care services which is often used to provide adolescent reproductive health information, but in its implementation the program is still not running optimally. One way to improve the reproductive health of young women is by providing education and stimulation on how to examine their own breasts (SaDaRi). The purpose of this study was to determine the Effectiveness of Peer Group Empowerment on Self-Breast Examination Behavior (SaDaRi) in Adolescent Girls at SMAK St. Thomas Morus Regency of Ende. The design / design used in this case study is True experimental using Pretest-Posttest Control Group Design. Researchers divided the group into two groups with different treatments, namely a control group of 30 people who were given health education through lectures from researchers and an experimental group of 30 people given a peer group model (peer group) with the Simple Random Sampling sampling technique. The results of this research is that there are significant differences in the level of knowledge of young women before and after health education with the Peer Group model on the behavior of breast self-examination (SaDaRi) between the experimental group and the control with p values ​​of 0.005 and 0.001. Based the results of the analysis above shows a significant increase in the level of knowledge of young women about Breast Self-Examination (SaDaRi) from before and after being given health education on the behavior of SaDaRi with the Peer Group model Keyword: Breast Cancer, Peer Group, Breast Self-Examination